Pengembangan LKPD Mata Pelajaran Kimia Berbasis Discovery Learning Pada Pokok Bahasan Termokimia Kelas XI - Nurlian Nurlian; Maysara; Saefuddin (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2023)
This study aims to determine the quality of discovery learning-based worksheets on thermochemical material and students' responses to the thermochemical material-based discovery learning worksheet products developed. The research method used is Research & Development (R&D) with the 4D model (Four D Models). The instrument used is in the form of assessment sheets/validation of student responses/responses. The results showed that the average validator assessment of the eligibility aspects of content, language and presentation had a percentage of 90.57% (very good) while the results of the student response analysis had a percentage of 89.19% (very good). From the results of this study it can be concluded that the LKPD Based on Discovery Learning on the thermochemical material developed has very good quality.